History of Turkish Air Force Aviation School and the Process of Transition to Air Force Academy - Osman YALÇIN (Gazi Akademik Bakış)
Turkish aviation has started as a military entity. The foundation of ‘’Tayyare Komisyonu’’ (Airplane Comission) in June 1, 1911 has been accepted as the official starting point. The organization of aviation includes pilot training, airplane supply, fondation of aviation school, establishment of combatant units, and building the air vehicles with local and national endeavour. Later, air defense systems, meteorology, training observers, machine specialist and technicians has gained importance as well. Turkish aviation has been built upon the ruins of the last wars of Ottoman Empire. After the invasion of the British and the French, Ottoman aviators moved to Maltepe and then to various parts of Anatolia eventually. During the Independence War, aviation school was founded in Eskişehir, moved to Adana, Konya, and came back to Adana again. After the Greek forces were expelled from Anatolia via İzmir, aviation school was moved to İzmir. In 1925, it was brought back to Eskişehir on October 1, 1951. After WWII, the duration of training in order to be a pilot was six years. In 1929, aviation school turned out to be an academic institution as well. On October 1, 1951, Air Force Academy was established in Eskişehir. Due to high sound of jet air planes, the academy was moved to İzmir in 1954. Education and training were restructured there and the quality was raised. In 1967, Air Force Academy was moved back to Yeşilköy where Turkish aviation was born some 47 years ago. Due to academic diversity and rich culture heritage, a productive period has started in Istanbul. Air Force Academy has been an institution offering BA level education since 2001 whose process goes back to 1990s. Around 90 civilian and 50 military academicians conduct education and research per year. Military training including Yalova encampment site, affective domain training, and sports activities are also conducted as well. With a 103 years history and around 16.000 graduates, Turkish Air Force Academy trains the staff who will safeguard the Turkish skies. Female cadets are also trained in Turkish Air force Academy with the same opportunities and priviliges as well.